1994
DOI: 10.1007/bf00315832
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of cytokeratin 18 and villin in type III alveolar cells (brush cells) of the rat lung

Abstract: Alveoli of the rat lung are lined by three different cell types, the flat type I cells and the cuboidal type II and type III cells. Type III cells differ from type II cells by the presence of an apical tuft of microvilli and the absence of lamellar type secretory granules. In the present study we show by double immunolabelling that type III cells of the rat lung can be identified at the light- and electron microscope level by antibodies against both cytokeratin 18 and the actin-crosslinking protein villin. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…This result is similar to the result of a previous 2-DE study that reported that phosphorylated Villin 2 protein was expressed during myoblast growth of C2C12 cells and was not expressed during early myogenesis (12). Generally, Villin 2 protein is called ezrin, and it is one the proteins that belong to ezrin-radixin-moesin (ERM) cytoskeleton-associated protein family (13)(14)(15). Villin 2 provides a crucial morphological link between the cell plasma membrane and the http://bmbreports.org BMB reports actin-based cytoskeleton (16,17), maintaining cell shape and polarity, and participating in cell migration, signaling, growth regulation, and differentiation (18,19).…”
Section: Functional Analysis Of Villin 2 Proteinsupporting
confidence: 90%
“…This result is similar to the result of a previous 2-DE study that reported that phosphorylated Villin 2 protein was expressed during myoblast growth of C2C12 cells and was not expressed during early myogenesis (12). Generally, Villin 2 protein is called ezrin, and it is one the proteins that belong to ezrin-radixin-moesin (ERM) cytoskeleton-associated protein family (13)(14)(15). Villin 2 provides a crucial morphological link between the cell plasma membrane and the http://bmbreports.org BMB reports actin-based cytoskeleton (16,17), maintaining cell shape and polarity, and participating in cell migration, signaling, growth regulation, and differentiation (18,19).…”
Section: Functional Analysis Of Villin 2 Proteinsupporting
confidence: 90%
“…1 F and G). This intermediate filament protein is present in considerably higher concentrations in brush cells than in any other epithelial cell type of the lung and the gastrointestinal epithelium (10). At low antibody concentrations, brush cells (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…§1734 solely to indicate this fact. against a-gustducin and the actin filament-bundling protein villin, a marker molecule for brush cells (10,12), identified these cells as brush cells (Fig. 1 D and E).…”
Section: Resultsmentioning
confidence: 93%
“…CK 18 belongs to the group of acidic keratins type I IF (Herrmann and Aebi 2000) that has been shown to be expressed in BCs of epithelia covering different organs of the GI tract (Kasper et al 1994). Because of the strong immunoreaction that BCs display after application of antibodies directed against CK peptide 18, these have been proposed and used as specific LM markers to identify BCs in various epithelia (Höfer and Drenckhahn 1996;Gebert et al 2000), although there are differences in species crossreactivity between antibody clones (Gebert et al 2000;and this study).…”
Section: Immunodetection Of Peripherinmentioning
confidence: 99%
“…Even in earlier detailed descriptions after thin-section transmission electron microscopy (Luciano et al 1968;Luciano and Reale 1969), two main characteristics of BCs were evident: the prominent microvillous brush border (from which they received their name; Rhodin and Dalhamn 1956) and the architecture of the cytoskeleton. The three building elements F-actin, microtubules, and intermediate filaments are uncommonly abundant and display an extremely ordered spatial arrangement and distribution in the cytoplasm (Luciano and Reale 1997 (Kasper et al 1994). Antibodies against CK 18 were then proposed and used as specific markers to identify BCs by light microscopy (Höfer and Drenckhahn 1996;Gebert et al 2000).…”
mentioning
confidence: 99%